LIQUIDITY AND MARKET RISK AS DETERMINANTS OF BANKS FINANCIAL PERFORMANCE - Marino Desponso; Tety Elida (Universitas Gunadarma, 2012)
The study aimed to analyze the influence of financial ratios such as Capital AdequacyRatio (CAR), BOPO, Net Interest Margin (NIM), Non-Performing Loan (NPL), and Loanto Deposit Ratio (LDR) on bank performance which is measured by Return on Asset(ROA). Data used is financial statements of 10 commercial banks during the years 2008-2011 with largest assets in Indonesia. This financial statement has been audited by BankIndonesia. Analysis technique used is multiple regression. The results showed that thefinancial performance (ROA) is influenced by market risks (NIM) and liquidity (LDR).Key Words: financial ratio, financial performance, commercial bank, risk market,liquidity risk